Psychometric validation and meaningful within‐patient change of the Migraine‐Specific Quality of Life questionnaire version 2.1 electronic patient‐reported outcome in patients with episodic and chronic migraine. Issue 3 (22nd January 2021) - Speck, Rebecca M.; Yu, Ren; Ford, Janet H.; Ayer, David W.; Bhandari, Rohit; Wyrwich, Kathleen W.
Abstract: Objective: To evaluate the measurement properties of all three domains of the Migraine‐Specific Quality of Life questionnaire version 2.1 (MSQ v2.1) electronic patient‐reported outcome (ePRO) to assess the functional impact of migraine in patients with episodic or chronic migraine (CM); and identify meaningful within‐patient change thresholds for the Role Function‐Restrictive (RFR), Role Function‐Preventive (RFP), and Emotional Function (EF) domains. Methods: Data were drawn from three double‐blind, placebo‐controlled, and randomized Phase 3 clinical studies (episodic migraine [EM]: EVOLVE‐1 and EVOLVE‐2; CM: REGAIN). The psychometric properties of the MSQ v2.1 ePRO domains were demonstrated by evaluating reliability (internal consistency and test–retest), construct validity (convergent and known groups), and responsiveness. Meaningful within‐patient change thresholds for domains were estimated using anchor‐based approaches, supplemented by empirical cumulative distribution function curves and probability density function plots to enable interpretation of meaningful change over 3 months. The Patient Global Impression of Severity (PGI‐S) and Patient Global Impression of Improvement served as anchors. Results: A total of 2, 850 patients with either EM (EVOLVE‐1: 851; EVOLVE‐2: 909) or CM (REGAIN: 1, 090) were included. The Cronbach's alpha estimates of internal consistency exceeded the recommended threshold of ≥0.70 for all domains from the three studies, indicating adequate internal consistency. Test–retest reliability intraclass correlation coefficients were ≥0.80 for all domains across all three studies, demonstrating almost perfect agreement. Convergent validity was supported by moderate‐to‐strong correlation ( r  ≥ 0.30) between all domains of MSQ v2.1 ePRO and studied anchors (Migraine Disability Assessment Score and PGI‐S scores) across all three studies. Known group validity was established between all domains and subgroups of patients stratified by baseline PGI‐S scores and baseline number of monthly migraine headache days for all three studies. The 3‐month meaningful within‐patient change thresholds were the same for EM and CM for RFP: 20.00 and EF: 26.67; and for RFR: 25.71. Conclusions: These findings demonstrate that all three domains of the MSQ v2.1 ePRO have sufficient reliability, validity, responsiveness, and appropriate interpretation standards. Our results suggest that MSQ v2.1 ePRO is a well‐defined and reliable patient‐reported outcome instrument that is suitable for use in clinical studies for evaluating the impact of migraine on patient functioning in episodic and CM.